Innovations in reaching farmers at scale: Novel bundling strategies for information, inputs, technology, and finance - Van Campenhout, Bjorn (International Food Policy Research Institute, 2023)
Presentation made at the Policy and Practice in Seed Sector Development in Uganda: An International Convening on Evidence and Action 11–12 December 2023 Entebbe, Uganda Imperial Botanical Beach Hotel